Karakterisasi dan Uji Aktivitas Antibakteri dari Fungi Endofit Ranting Tanaman Manggis (Garcinia mangostana L.) terhadap Escherichia coli dan Staphylococcus aureus - Widjaja, Kevin; Soegianto, Lisa; Ervina, Martha (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2019)
Resistance is commonly caused by improper usage of antibiotics, so the treatment of the infection always needs a new and more potent compounds. Endophytic microbes are microbes that all or part of its life stay in the tissues of plant, which established a mutually beneficial relationship between them. In this research, isolation of endophytic fungi was conducted by sticking the sterilized twigs of mangosteen to the media Malt Extract Agar obtained three pure endophytic fungi colonies. The antibacterial activity assay with direct inoculation method at media Plate Count Agar which was inoculated with bacteria and showed that the antibacterial activity against Escherichia coli ATCC 8739 was one isolate (ER2) with inhibition average ratio 1.42 and against Staphylococcus aureus ATCC 6538 was three isolates (ER1, ER2, and ER3) with inhibition average ratio 1.66; 1.37; and 1.89. The fungus were observed characteristics of the macroscopic, microscopic and biochemical assay. ER1 and ER3 isolates are suspected as a Penicillium genus with specific characteristics such as the conidiophore, fialid, metulae, and conidiospore. ER2 isolate was suspected as a Rhizoctonia genus because there are nearly right-angled hyphae and monilioid cells.